2023
DOI: 10.3390/diagnostics13061088
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Deep Learning Method for Detection of Invasive Parkinson’s Disease

Abstract: Parkinson’s disease directly affects the nervous system are causes a change in voice, lower efficiency in daily routine tasks, failure of organs, and death. As an estimate, nearly ten million people are suffering from Parkinson’s disease worldwide, and this number is increasing day by day. The main cause of an increase in Parkinson’s disease patients is the unavailability of reliable procedures for diagnosing Parkinson’s disease. In the literature, we observed different methods for diagnosing Parkinson’s disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Studies have explored the development of artificial intelligence tools for predicting vocal cord pathology in primary care settings [63]. Additionally, the application of convolutional neural network ensembles and deep learning methods has been investigated for the detection of Parkinson's disease from voice recordings, demonstrating the potential of smartphone-based voice analysis in disease detection [64,65]. Furthermore, research has shown the association of noninvasive vocal biomarkers with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [66], highlighting the potential of smartphone-based voice analysis in infectious disease detection [67].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have explored the development of artificial intelligence tools for predicting vocal cord pathology in primary care settings [63]. Additionally, the application of convolutional neural network ensembles and deep learning methods has been investigated for the detection of Parkinson's disease from voice recordings, demonstrating the potential of smartphone-based voice analysis in disease detection [64,65]. Furthermore, research has shown the association of noninvasive vocal biomarkers with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [66], highlighting the potential of smartphone-based voice analysis in infectious disease detection [67].…”
Section: Discussionmentioning
confidence: 99%